Potential effects of scaling-up infrastructure in Peru: a general equilibrium model-based analysis. Issue 27 (8th June 2020) - Montaud, Jean-Marc; Dávalos, Jorge; Pécastaing, Nicolas
ABSTRACT: This study assesses and compares the potential economic impacts of different investment plans dedicated to filling infrastructure gaps in Peru. Using a national database at the firm level, we start by estimating empirically the positive externalities of Peruvian infrastructure, such as energy, telecommunications, and transportation facilities, on the output of private activities. In the second step, these estimates are introduced in a dynamic computable general equilibrium model used to conduct counterfactual simulations of various investment plans in infrastructure over a 15-year period. These simulations show first to what extent scaling-up infrastructure could be a worthwhile strategy to achieve economic growth in Peru; however, they also show that these benefits depend on the choice of funding schemes related to such public spending.